Mechanical, Thermal Properties and Hirshfeld Surface Analysis of N-Acetylglycine Single Crystal - Thanigaiarasu, V.J.; Kanagathara, N.; Usha, R.; Sabari, V.; Natarajan, V. (Asian Journal of Chemistry, 2020)
Mechanical properties of some amino acid based derivatives plays a versatile role in the device fabrication due to its mechanical strength. One such acetyl derivative of glycine named N-acetylglycine has been taken in the present study for investigation. Hardness analysis has been carried out on the grown crystal with various loads and it was observed that Vicker’s hardness number (Hv) varied for different loads. The work hardening coefficient is calculated to be 1.628 which confirms that the grown crystal comes under moderately hard material category. Other mechanical parameters like minimum load indentation (W), materials constant (k1), load dependent constant (A1) and elastic stiffness constant (C11) have also been calculated. The thermal analysis has also been carried and it reveals that the complete weight loss of N-acetylglycine starts from 208.60 ºC and ends at 281.58 ºC. The corresponding DTA peak is observed at 217.97 ºC which is the melting point of the sample. As expected, there is no phase transition till the material melts and this enhances the temperature range for the utility of the crystal. Kinetic and thermodynamic parameters have been calculated. All the results obtained from hardness as well as thermal measurement confirm the material may be suitable for electro-optic device applications. Further, the 3D Hirshfeld surface analysis and 2D fingerprint maps gives deep insight into the intermolecular interactions between the compound.